Study of arbitrary waveform generation for software defined radio - Luo, Jia Yu. (2010)
WiMAX is a digital communication system based on IEEE 802.16d-2004 and IEEE 802.16e-2005 air-interface standards. It can provide excellent non line of sight (NLOS) coverage while many technologies currently can only provide line of sight coverage. In this report, I shall introduce some basic information of WiMAX, including WiMAX forum, its application and so on. Next, I shall provide the detailed steps of generating WiMAX signal using MATLAB and SMBV 100A Vector Signal Generator. The focus will be on the MATLAB algorithm. Then, by comparing and analyzing the MATLAB simulation results and generated signals, I shall validate the simulation results. Figures, tables and equations are provided in the report. The MATLAB algorithm is attached in Appendix.